Event-Driven Observer-Based Smart-Sensors for Output Feedback Control of Linear Systems - Acho, Leonardo (Sensors (Basel, Switzerland), 2017)
This paper deals with a recent design of event-driven observer-based smart sensors for output feedback control of linear systems. We re-design the triggering mechanism proposed in a previously reported system with the implementation of self-sampling data smart sensors; as a result, we improve its performance. Our approach is theoretically supported by using Lyapunov theory and numerically evidenced by controlling the inverted pendulum on the cart mechanism.